2012
DOI: 10.1177/0954407012447020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pressure losses in a common rail diesel injector

Abstract: A methodology to characterise the pressure losses in quasi-steady conditions (i.e. at full needle lift) of common rail diesel injectors was developed. The aim was to quantify the error when experimental results of nozzle internal flow are compared with CFD results, where pressure losses are usually neglected. The proposed methodology is based mainly on experimental tests that are complemented with some approximate calculations, based on the physics of the phenomenon, to take into account the effect of the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…At the same time, the flow area between nozzle volume and needle chamber increases with the rising of the needle lift, which improves the fuel injection rate. 36 As a result, the fuel pressure in the system changes sharply and the stability of the system is destroyed. It could be seen from Figure 12(e) that the eigenvalues distribute in both of the positive and negative half plane of the real axis, namely, the system is in unstable state again.…”
Section: Distribution Of Eigenvalue For the State Matrixmentioning
confidence: 99%
“…At the same time, the flow area between nozzle volume and needle chamber increases with the rising of the needle lift, which improves the fuel injection rate. 36 As a result, the fuel pressure in the system changes sharply and the stability of the system is destroyed. It could be seen from Figure 12(e) that the eigenvalues distribute in both of the positive and negative half plane of the real axis, namely, the system is in unstable state again.…”
Section: Distribution Of Eigenvalue For the State Matrixmentioning
confidence: 99%
“…An efficient combustion process in engines such as direct injection (DI) Diesel engines and gasoline direct injection (GDI) engines, clearly depends on the characteristics of the own injection process and, in consequence, the later air-fuel mixing process. 1 However, although in the last decade the experimental facilities 2,3 and procedures 4,5 have experimented a great quality increase and better performance, the development of the simulation methods (zero-dimensional, [6][7][8] one dimensional, 9,10 and/or tri-dimensional methods [11][12][13] ) have become these tools in the most important tool for a better understanding of such complex process.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the dimensions and condition of the spray hole surface significantly affects the flow properties of injector nozzles, and this, in turn, determines the size and form of fuel jets dosed to individual cylinders of a diesel engine and the quality of fuel atomization. Many investigations have shown that the nozzle hole geometry and its internal flow characteristics play an essential role in the spray formation [2,12,16,17] and combustion process [7,8,14,18].…”
Section: Introductionmentioning
confidence: 99%